450 hystero-Tubal hidrotubaciones made in the Peruvian Center for Fertility Marriage - Ascenzo Cabello, Jorge (2015)
Hystero-tubal hidrotubaciones practice in all cases "Tubal Factor" committed with certainty, whether or not another factor Matrimonial Sterility. 9 indicate hidrotubaciones, cycle 3, for 3 months, the 4th cycle check results. We describe the technique of hidrotubaciones and contraindications.